Analisi Komparatif Penerapan Fatwa Dewan Syariah Nasional (DSN) MUI Nomor 115/DSN-MUI/IX/2017 Tentang Akad Mudharabah Dengan Perjanjian Pembiayaan Mudharabah Pada Bank Syariah Indonesia Cabang Bima - Nur Imamah; Muhammad Rasyad Al Fajar; Muhammad Zia Ulhaq (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to describe: First, How is the Mudharabah Financing Agreement Arranged in the Fatwa of the National Sharia Council (DSN) MUI Number 115/DSN-MUI/IX/2017 Concerning the Mudharabah Contract? Second, How is the Mudharabah Financing Agreement in Sharia Banking in Bima City? and third, How is the Comparison of the Mudharabah Agreement between the MUI Fatwa Number 115/DSN-MUI/IX/2017 Concerning the Mudharabah Contract with the Mudharabah Agreement at BSI? The approach method used in this study is a qualitative approach with a descriptive-analytical research type. While the Research Results obtained, Based on Law Number 21 of 2008, the mudharabah contract has strong legal legitimacy as a sharia-based financing that emphasizes justice, partnership, transparency, and prudence. This contract represents a trust relationship between shahibul maal and mudharib that is free from usury, gharar, and maysir. DSN-MUI Fatwa No. 115/DSN-MUI/IX/2017 emphasizes profit sharing based on a ratio, as well as regulating losses and guarantees to prevent moral hazard. Implementation at the BSI Bima City Branch has complied with the legal framework and fatwa, despite facing challenges in MSME literacy and management. BSI remains active in education, empowerment, and dispute resolution through deliberation.